2007
DOI: 10.1002/rcm.2886
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of 2,4,6‐trihydroxyacetophenone as matrix and enzymatic deglycosylation in organic‐aqueous solvent systems for the simultaneous characterization of complex glycoproteins and N‐glycans by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry

Abstract: Phenomenal! The activity of the palladium–phenanthroline catalytic system for the carbonylation of nitrobenzene to methyl phenylcarbamate is greatly enhanced by the addition of phosphorus acids. Of those that were studied, the best promoter is the very cheap, easily separable, and nontoxic phosphoric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Signal intensity was also increased if 10 mM sodium chloride was added to the matrix . Fenaille et al (2007a) have shown that THAP is a more efficient matrix than the more commonly used sinapinic acid for ionization of glycoproteins, even those with masses as high as 150 kDa. Singly charged ions were the major species produced but the larger glycoproteins yielded both doubly and triply charged ions in addition.…”
Section: B Simple Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal intensity was also increased if 10 mM sodium chloride was added to the matrix . Fenaille et al (2007a) have shown that THAP is a more efficient matrix than the more commonly used sinapinic acid for ionization of glycoproteins, even those with masses as high as 150 kDa. Singly charged ions were the major species produced but the larger glycoproteins yielded both doubly and triply charged ions in addition.…”
Section: B Simple Matricesmentioning
confidence: 99%
“…Under these conditions, deglycosylation was much more efficient than when reactions were conducted in water or buffers. Most glycoproteins could be deglycosylated in 1 hr at 378C and, furthermore, because of the absence of salts, etc., the mixture could be examined directly by MALDI (Fenaille et al, 2007a).…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 99%
“…FVIIa was enzymatically digested using PNGase F and Endo H in organic-aqueous solvent systems [22]. Briefly, 1 μL of a FVIIa aqueous solution (i.e.…”
Section: Estimation Of N-glycan Composition By Endoglycosidase Digestmentioning
confidence: 99%
“…Analyses were carried out using different matrix solutions: (i) HCCA, 0.3 mg/mL in ethanol/acetone (2:1, v/v); (ii) DHB, 20 mg/mL in acetonitrile; (iii) THAP, 10 mg/mL in acetonitrile/water (1:1, v/v) containing 0.1% TFA. HCCA and DHB matrices were used for the analysis of proteolytic peptides and glycopeptides, respectively; THAP was used for the analysis of native and deglycosylated proteins (Fenaille et al 2007). For each sample, 0.5 µL of analyte solution and 0.5 µL of matrix solution were deposited and thoroughly mixed on the target.…”
Section: Maldi-tofms Analysesmentioning
confidence: 99%
“…CFH was enzymatically digested using PNGase F and Endo H in organic-aqueous solvent systems (Fenaille et al 2007). Briefly, 1 µL of a CFH aqueous solution (i.e., 2 µg) was mixed with 6 µL of acetonitrile/water (75:25, v/v) and 0.5 µL of a PNGase F (i.e., 1.25 mU) or Endo H solution (i.e., 2.5 mU).…”
Section: Deglycosylation Of Cfh For Maldi-tofms Analysismentioning
confidence: 99%